Evaluation of Stemona collinsiae root extracts for topical cockroach control: adulticidal, nymphicidal, and chemical distribution analysis - Aurapa Sakulpanich; Anon Phayakkaphon; Korawan Ounklong; Jinnaphat Sommanat; Yudthana Samung; Raweewan Srisawat; Jiraporn Ruangsittichai (Toxicon: X)
Stemona collinsiae root extracts have been scientifically shown to exhibit antifeedant, growth inhibitory, larvicidal, pupacidal, and adulticidal activities in pests and insect vectors. In this research, contact toxicity of hexane, dichloromethane, ethanol, and water extracts was repeatedly tested on final-instar nymphs and adult Periplaneta americana using a topical application method and the penetration and distribution of didehydrostemofoline were detected at each of the specified times using MALDI-IMS and HPLC. Dichloromethane extract, which contained the highest didehydrostemofoline content, exhibited the highest contact toxicity against final-instar nymphs (41.0–100.0 % corrected mortality) and adult Periplaneta americana (23.0–46.0 % corrected mortality), while P. americana exposed to the water extract survived (0.0 % corrected mortality), similar to negative control group (0.0 % corrected mortality). Signs of toxicity such as excited movement, tremors, depression, motionlessness, expanded abdomen, and affected alimentary canal were observed in P. americana exposed to dichloromethane and hexane extracts. MALDI-IMS images showed that didehydrostemofoline was able to distribute from the sectioned first-abdominal segment to the sectioned head segment. HPLC chromatograms of the extracts of abdominal integument, lipid layer, alimentary canal, and head segment, it revealed that didehydrostemofoline initially adhered to the epicuticle, then penetrated through deeper layers of the integument and was distributed to other tissues. Therefore, P. americana could absorb didehydrostemofoline via topical administration, which was subsequently distributed and transported to other tissues. S. collinsiae dichloromethane root extract containing didehydrostemofoline could potentially be used as active ingredients in cockroach control.